Impact of CPAP and ventilator system resistance on respiratory effort in healthy volunteers - Simon Lindner; Lena Doerflinger; Luisa S. Drotleff; Burcu Link; Benjamin Neetz; Julia D. Michels-Zetsche; Felix J. F. Herth; Daniel Duerschmied; Simone Britsch (BMC Pulmonary Medicine, 2026)
Abstract Introduction Continuous positive airway pressure (CPAP) is widely used for the treatment of acute and chronic respiratory failure and inspiratory support pressure (ΔP insp ) can be added to achieve non-invasive ventilation (NIV). We performed a physiological study to determine the effect of CPAP and inspiratory support pressure on respiratory effort measured by esophageal tidal swings in healthy volunteers. Methods Esophageal tidal swings were measured in spontaneously breathing, healthy volunteers undergoing 4 airway pressure conditions: atmospheric pressure (A), on a ventilator without any applied pressures (V), CPAP of 5 cmH 2 O, and NIV with PEEP of 5 cmH 2 O and ΔP insp of 5 cmH 2 O during rest, light, and strenuous exercise. The sequence of airway conditions was randomized and the investigator reading the esophageal pressures was blinded. Results Thirty-eight individuals were included in the analysis. Esophageal tidal swing during rest was highest when CPAP was applied, compared to A and NIV. During light and strenuous exercise, both V and CPAP increased respiratory effort, compared to A and NIV, suggesting an increase in ventilator system resistance at higher minute ventilation. Conclusion CPAP increased respiratory effort compared to both NIV and breathing at atmospheric pressure, but ventilator system resistance appeared to be a more relevant determinant of respiratory effort at higher minute ventilation induced by exercise. As acute respiratory failure often is associated with high minute ventilation, further studies are needed to examine the potential clinical implications of these findings.